Operational strategies to achieve and maintain malaria elimination. - Moonen, B; Cohen, J; Snow, R; Slutsker, L; Drakeley, C; Smith, D; Abeyasinghe, R; Rodriguez, M; Maharaj, R; Tanner, M; Targett, G (2010)
Present elimination strategies are based on recommendations derived during the Global Malaria Eradication Program of the 1960s. However, many countries considering elimination nowadays have high intrinsic transmission potential and, without the support of a regional campaign, have to deal with the constant threat of imported cases of the disease, emphasising the need to revisit the strategies on which contemporary elimination programmes are based. To eliminate malaria, programmes need to concentrate on identification and elimination of foci of infections through both passive and active methods of case detection. This approach needs appropriate treatment of both clinical cases and asymptomatic infections, combined with targeted vector control. Draining of infectious pools entirely will not be sufficient since they could be replenished by imported malaria. Elimination will thus additionally need identification and treatment of incoming infections before they lead to transmission, or, more realistically, embarking on regional initiatives to dry up importation at its source.